Inhibition of All-Trans Retinoic Acid on the Expression of the Genes Envoled in Self-Renewal and Notch Signaling Pathway in Gastric Cancer Cells - Phu Hung, Nguyen; Thi Binh, Luu; Thi Thanh Huong, Le; Thi Huong Giang, Diep (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4787, 2018)
Abstract: All-trans retinoic acid (ATRA) plays an important role in many cellular processes and is a potentially promising substance for cancer therapy. The self-renewal, a prominent feature of cancer stem cells, is tightly controlled by a number of specific genes and is mediated by the cell signaling pathways. The Notch signal pathway has been shown to be one of the few major molecular signaling pathways of cancer stem cells, which regulates the self-renewal and survival of cancer stem cells. This study shows that ATRA reduced the expression of important genes involved in self-renewal of cells, including Sox2, KLF4, DMNT1 and MYC as well as TBGUT markers such as CD24, MUC1 and CD90. Furthermore, it is indicated that the ATRA-induced expression of self-renewal genes and cancer stem cell markers of gastric cancer stem cells can be mediated by the regulation of the Notch signaling pathway. Keywords: All-trans retinoic acid, gastric cancer stem cell, Notch signaling pathway. References [1] Dupé, V., Ghyselinck, N.B., Thomazy, V., Nagy, L., Davies, P.J., Chambon, P., and Mark, M, Essential roles of retinoic acid signaling in interdigital apoptosis and control of BMP-7 expression in mouse autopods, Development Biology, 208 (1999) 30. [2] Altucci, L., and Gronemeyer, H. The promise of retinoids to fight against cancer, Nature Reviews Cancer, 1 (2001) 181. [3] Aguirre, A., Rubio, M.E., and Gallo, V. Notch and EGFR pathway interaction regulates neural stem cell number and self-renewal, Nature, 467 (2010) 323. [4] Weng, A.P., Millholland, J.M., Yashiro-Ohtani, Y., Arcangeli, M.L., Lau, A., Wai, C., Del Bianco, C., Rodriguez, C.G., Sai, H., Tobias, J, c-Myc is an important direct target of Notch1 in T-cell acute lymphoblastic leukemia/lymphoma, Genes Development, 20 (2006) 2096. [5] Efstratiadis, A., Szabolcs, M., and Klinakis, A. Notch, Myc and breast cancer, Cell Cycle, 6 (2007) 418. [6] Ishiguro, T., Ohata, H., Sato, A., Yamawaki, K., Enomoto, T., and Okamoto, K, Tumor-derived spheroids: Relevance to cancer stem cells and clinical applications, Cancer Science, 108 (2017) 283. [7] Al-Hajj, M., and Clarke, M.F. Self-renewal and solid tumor stem cells, Oncogene, 23 (2004) 7274. [8] Basu-Roy, U., Seo, E., Ramanathapuram, L., Rapp, T.B., Perry, J.A., Orkin, S.H., Mansukhani, A., and Basilico, C, Sox2 maintains self renewal of tumor-initiating cells in osteosarcomas, Oncogene, 31 (2012) 2270. [9] Jiang, J., Chan, Y.-S., Loh, Y.-H., Cai, J., Tong, G.-Q., Lim, C.-A., Robson, P., Zhong, S., and Ng, H.-H, A core Klf circuitry regulates self-renewal of embryonic stem cells, Nature Cell Biology, 10 (2008) 353. [10] Lakshminarayanan, V., Supekar, N.T., Wei, J., McCurry, D.B., Dueck, A.C., Kosiorek, H.E., Trivedi, P.P., Bradley, J.M., Madsen, C.S., Pathangey, L.B, MUC1 Vaccines, Comprised of Glycosylated or Non-Glycosylated Peptides or Tumor-Derived MUC1, Can Circumvent Immunoediting to Control Tumor Growth in MUC1 Transgenic Mice, PloS One, 11 (2016) 0145920. [11] Wang, X., Wang, C., Zhang, X., Hua, R., Gan, L., Huang, M., Zhao, L., Ni, S., and Guo, W, Bmi-1 regulates stem cell-like properties of gastric cancer cells via modulating miRNA, Journal of Hematology and Oncololgy, 9 (2016) 90. [12] Al-Hajj, M., Wicha, M.S., Benito-Hernandez, A., Morrison, S.J., and Clarke, M.F, Prospective identification of tumorigenic breast cancer cells. Proceedings of the National Academy of Sciences, 11 (2003) 6890. [13] Wang, X.-T., Kong, F.-B., Mai, W., Li, L., and Pang, L.-M, MUC1 Immunohistochemical Expression as a Prognostic Factor in Gastric Cancer: Meta-Analysis. Disease Markers, 2016 (2016) 9421571. [14] Zeng, L.-X., Tang, Y., and Ma, Y, Ataxin-3 expression correlates with the clinicopathologic features of gastric cancer. International Journal of Clinical and Experimental Medicine, 7 (2014) 973. [15] Kang, H., An, H.-J., Song, J.-Y., Kim, T.-H., Heo, J.-H., Ahn, D.-H., and Kim, G, Notch3 and Jagged2 contribute to gastric cancer development and to glandular differentiation associated with MUC2 and MUC5AC expression, Histopathology, 61 (2012) 576. [16] Sun, Y., Gao, X., Liu, J., Kong, Q.-Y., Wang, X.-W., Chen, X.-Y., Wang, Q., Cheng, Y.-F., Qu, X.-X., and Li, H, Differential Notch1 and Notch2 expression and frequent activation of Notch signaling in gastric cancers, Archives of Pathology & Laboratory Medicine, 135 (2011) 451. [17] Yeh, T.-S., Wu, C.-W., Hsu, K.-W., Liao, W.-J., Yang, M.-C., Li, A.F.-Y., Wang, A.-M., Kuo, M.-L., and Chi, C.-W, The activated Notch1 signal pathway is associated with gastric cancer progression through cyclooxygenase-2, Cancer Research, 69 (2009) 5039. [18] Tseng, Y.-C., Tsai, Y.-H., Tseng, M.-J., Hsu, K.-W., Yang, M.-C., Huang, K.-H., Li, A.F.-Y., Chi, C.-W., Hsieh, R.-H., Ku, H.-H., Notch2-induced COX-2 expression enhancing gastric cancer progression, Molecular Carcinogenesis, 51 (2012) 939.